Impactos cirSurgical Impacts on Pregnant Women with Autoimmune Diseases úrgicos em gestantes com doenças autoimunes - Wictor Lima dos Santos, Luis; Xavier Valenzuela , Laura; Espindola da Cruz, Giovanna; Regis Rodrigues dos Santos , Raul; Karoliny Lima dos Santos, Witória; Virginia Borges Souza de Aquino Coelho, Dioelen (Brazilian Journal of Implantology and Health Sciences, 2025)
When analyzing the scenario of autoimmune diseases during pregnancy, a challenging picture was identified, as hormonal and immune changes in pregnancy can worsen symptoms and increase the likelihood of complications. This article was developed with the aim of exploring the surgical impacts on pregnant women with autoimmune diseases, evaluating the associated risks and complications that could interfere with pregnancy. The methodology involved a systematic review conducted in the PubMed, LILACS, and SciELO databases, using the descriptors "autoimmune", "complications", "surgery", and "pregnant". Studies published in the last five years and presenting relevant data on the addressed topic were filtered. Exclusion criteria included studies that did not specify maternal and fetal clinical outcomes or did not provide sufficient information for analysis. It is emphasized that managing these patients requires a multidisciplinary approach to ensure safety during interventions. Specialized and individualized protocols are essential to reduce risks and improve maternal and fetal clinical outcomes.